Efficacy of Water Resistance Therapy in Subjects Diagnosed With Behavioral Dysphonia: A Randomized Controlled Trial - Guzman, Marco; Jara, Rodrigo; Olavarria, Christian; Caceres, Paloma; Escuti, Geordette; Medina, Fernanda; Medina, Laura; Madrid, Sofia; Muñoz, Daniel; Laukkanen, Anne-Maria (Journal of voice, 2017)
The purpose of the present study was to determine the efficacy of water resistance therapy (WRT) in a long-term period of voice treatment in subjects diagnosed with voice disorders. Twenty participants, with behavioral dysphonia, were randomly assigned to one of two treatment groups: (1) voice treatment with WRT, and (2) voice treatment with tube phonation with the distal end in air (TPA). Before and after voice therapy, participants underwent aerodynamic, electroglottographic, acoustic, and auditory-perceptual assessments. The Voice Handicap Index and self-assessment of resonant voice quality were also performed. The treatment included eight voice therapy sessions. For the WRT group, the exercises consisted of a sequence of five phonatory tasks performed with a drinking straw submerged 5 cm into water. For the TPA, the exercises consisted of the same phonatory tasks, and all of them were performed into the same straw but the distal end was in air. Wilcoxon test showed significant improvements for both groups for Voice Handicap Index (decrease), subglottic pressure (decrease), phonation threshold pressure (decrease), and self-perception of resonant voice quality (increase). Improvement in auditory-perceptual assessment was found only for the TPA group. No significant differences were found for any acoustic or electroglottographic variables. No significant differences were found between WRT and TPA groups for any variable. WRT and TPA may improve voice function and self-perceived voice quality in individuals with behavioral dysphonia. No differences between these therapy protocols should be expected.